Does gentrification of the Praga Północ district in Warsaw really exist? - Dudek-Mańkowska, Sylwia; Iwańczak, Bartłomiej (Bulletin of Geography. Socio-economic Series, 2018)
Research on gentrification has been conducted for over 50 years by representatives of many disciplines. Modern gentrification is a process somewhat different from that originally described by R. Glass in 1964. Authors do not agree how to measure the process, nor how to explain its meaning (Bourne, 1993). Creating the right indicators is very difficult, especially if it is widely believed that gentrification, as a process identifying changes over time and a way of measuring dynamics, should enable the comparison of data from multiple years (Lees, 2010). The aim of this study was to identify the socio-spatial changes taking place in the Warsaw district of Praga Północ and to determine if it can be described as gentrification. The study area is a district stereotypically perceived as neglected, dangerous and deteriorated (e.g. Dudek-Mańkowska, 2011), at the same time subject to strong functional changes. Praga Północ is also an area of interest to many artists, creative industries and developers, and is undergoing gradual regeneration through municipal urban revitalization programs. It is also an area that the media portray as undergoing the process of gentrification. The results show that social and residential changes actually take place but the overall gentrification has not been felt by residents.